Large inflamed facial cysts in teenagers. Issue 6 (19th September 2020) - Meister, Harry; Shihab, Nahla; Lebwohl, Mark; Silverberg, Nanette B.
Abstract: Background: Facial cysts can become large (1‐5 cm) or giant (>5 cm) on the face. Objective: To describe the medical course of large and giant facial cysts in adolescents. Methods: A case series of 11 patients with large or giant facial cysts seen in an outpatient pediatric dermatology practice. Results: Seven patients underwent incision and drainage with culture of cyst contents growing Cutibacterium acnes in six, while the seventh grew Cutibacterium acnes from a frequently worn hat. All patients were treated with traditional therapeutics for cystic acne including intralesional triamcinolone (n = 9), oral antibiotics (n = 10), and isotretinoin (n = 1). Three patients who did not undergo cyst drainage had persistent symptomatology requiring cyst excision, whereas the seven patients whose cysts were drained (3 on initial management and 4 after recurrence) eventually had complete healing without need for surgery. Conclusion: Incision and drainage (I & D) and culture of cyst contents can identify cases of cysts related to Cutibacterium acnes . For some cases of large facial cysts related to Cutibacterium acne, I&D combined with conservative acne management (using standard acne guidelines) can prevent the need for surgical excision in some patients. Prospective studies are needed to determine whether this combination of therapy leads to best outcomes clinically and cosmetically.